Strategic capacities in Dutch water management and spatial planning - Johan Woltjer; Niels Al (European Regional Science Association (ERSA), 2005)
Dutch water management currently is in a position of fundamental change and renewal. As a consequence of factors such as climate change, continuous land subsidence, urbanisation pressures, and a lacking natural resilience of the water system to absorb water surpluses and shortages, the emphases has shifted from technical measures such as heightening dikes and enlarging drainage capacities towards allowing water to take more space. Since the late 1990s, water management has been modified from an approach of 'keeping it out' towards 'fitting it in'. As a consequence, 'water management' and 'spatial planning' are associated more closely, especially at the regional level of scale. Recent efforts by spatial planners and water managers to establish new connections have been mainly oriented towards a regulatory planning style: mutual reviewing of policy documents, the interchange of technical knowledge, the establishment of new legal instruments, and the imposition of norms and standards. The paper provides an overview of these efforts, and then introduces the observation that a supplementary strategic planning style would be helpful. Further attunement between 'space' and 'water' requires strategic capacities to 'frame mindsets', 'to organise attention', and to transform restrictions into opportunities. Based on a literature review and case studies, therefore, we raise some critical questions as to how efforts to synchronise regional water management and spatial planning match international insights in strategy making and capacity building. Following Healey et al., we understand regional strategy making to include a notion of providing regions with 'institutional capacity' and social, intellectual, and political capital. We also build on Mintzberg et al. to emphasise the importance of 'real vision' and the need for more 'imagination applied to building a strategy'. To what extent can current attempts to link Dutch water management and spatial planning be regarded as a reflection of a more strategic planning style? How do prevailing institutional conditions offer constraints or opportunities for further strategic action? We employ the Dutch case to explore some of these exemplary questions.
Keywords: 330